ANALISIS PEMILIHAN SUPPLIER UNTUK PEMESANAN BAHAN BAKU YANG OPTIMAL MENGGUNAKAN METODE AHP DAN FUZZY AHP: STUDI KASUS DI PT XYZ - Nunung Nurhasanah; Muhamad Aqil Tamam (JURNAL TEKNIK INDUSTRI, 2013)
The availability of wheat flour as raw material is a crusial planning, especially forPT. XYZ. That is why, this availability needs to be maintained, thus whenever industry needsto produce noodle, wheat flour always available as stock.PT. XYZ has several suppliers tosupply wheat flour in present.But, in order to fulfill the supplies, PT. XYZ used to get theirlost because of the rejected and lateness of wheat flour as raw materials.In other way, thiscompany has not yet had a standard method to choose the best supplier.This research has studied by using two methods in order to choose the best suppleirs.These are Analitical Hierarchy Process (AHP) and Fuzzy AHP. This research has alsostudied to fulfill the optimal raw material order. In order to get the optimal order quantity,this research suggested Economic Order Quantity (EOQ) modeling.This research has shown that there are no significant deferences between AHP andFuzzy AHP. Based on this research, PT. XYZ may use either AHP or Fuzzy AHP to choosethe best supplier. Based on EOQ, the optimal order quantity is 103.730kg, and companyshould order every 23 days, meaning there is 16 times order to supplier. The reorderpoint is 22.230kg, and the total cost is Rp.9.923.475.086.